Terrorism and Employment: Evidence from Successful and Failed Terror Attacks - Abel Brodeur (Institute for the Study of Labor (IZA), 2015)
This paper examines the economic consequences of terror attacks and the channels through which terrorism affects local economies. I rely on an exhaustive list of terror attacks over the period 1970-2013 in the U.S. and exploit the inherent randomness in the success or failure of terror attacks to identify the economic impacts of terrorism. The findings suggest that successful attacks, in comparison to failed attacks, reduce the number of jobs in targeted counties by approximately 5% in the year the attack takes place. The effects fade away after 2 years and I find no evidence that neighboring counties suffer from the successful attack. Analyzing the channels, I find suggestive evidence that the decrease in the physical capital stock of a county partially explains the temporary reduction in jobs. I also focus on economic attitudes and political preferences since these preferences have been shown to be related to economic outcomes. The results suggest that successful attacks decrease temporarily vote share for Democrat candidates in gubernatorial elections and bring a leftward shift in attitudes in targeted counties.
Keywords: D72; D74; C13; P16; 330; crime; terrorism; growth; preferences; voting behavior